1992
DOI: 10.1017/s0047404500015293
|View full text |Cite
|
Sign up to set email alerts
|

How taboo are taboo words for girls?

Abstract: In the past five years, there has been much interest in the question of whether women are really as concerned about politeness and status as they have been made out to be by such writers as Baroni and D'Urso (1984), Crosby and Nyquist (1977), Lakoff (1973), Spender (1980), and Trudgill (1972. Despite the commonly held perception that it is only males who bandy about derogatory and taboo words (Bailey 1985;Flexner 1975), Risch (1987) provided counterevidence based on data obtained in the United States. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(31 citation statements)
references
References 12 publications
(14 reference statements)
0
30
0
1
Order By: Relevance
“…However, swearing is taken much more lightly if done among friends who generally accept such behavior and in situations where offenders know their words will not be held against them (Mercury, 1995;Staley, 1978). It is generally socially unacceptable for adults to cuss in front of children (Arango, 1989;Foote & Woodward, 1973) and for children to swear in front of adults (DeKlerk, 1992).…”
Section: Contextmentioning
confidence: 99%
“…However, swearing is taken much more lightly if done among friends who generally accept such behavior and in situations where offenders know their words will not be held against them (Mercury, 1995;Staley, 1978). It is generally socially unacceptable for adults to cuss in front of children (Arango, 1989;Foote & Woodward, 1973) and for children to swear in front of adults (DeKlerk, 1992).…”
Section: Contextmentioning
confidence: 99%
“…De Klerk (1992) also did a research in South Africa and strongly supported Risch's findings and "challenged the assumption that women stick to standard speech" (De Klerk, 1992) . De Klerk's study rejected the idea that males use more or taboo words than women.…”
Section: Discussionmentioning
confidence: 86%
“…Female respondents also commonly believed that in most of the contexts stated in the questionnaire, the use of swearing was less proper than males did. De Klerk (1991Klerk ( , 1992 also found that males displayed a greater tolerance for the use of swear words than females. Research shows that the frequency and strength of swearing for both sexes depend on factors, such as social networks, social status, age, and education (Hughes, 1992;De Klerk, 1991, Stapleton, 2003.…”
Section: Introductionmentioning
confidence: 93%